Problems of analysing quest or reconstruction of meaning after traumatic loss - Klimaitė, Vaiva (Psichologija, 2014)
In the literature on grief and loss, it is noticed that the quest or the reconstruction of meaning after a traumatic loss of significant others has a crucial impact on successfull coping with this traumatic experience. Existing research proves that traumatic loss strongly shatters the system of meaning of a trauma survivor, and thus it becomes harder to integrate this experience into the self structures or personal memory. This relation between quest or the reconstruction of meaninng and difficulties to cope with traumatic loss is a multidimensional process. Authors investigating it frequently get quite controversial results. However, it is necessary to combine and compare studies made in this field and to summarize the knowledge of quest or reconstruction of meaning having or not an impact on coping with traumatic loss. There, several problematic aspects emerge. One of the basic ones is that there are some attempts to generalize the process of grief after traumatic and other very different losses and the role of quest or reconstruction of meaning in this process. The problems may arise because different researchers have different attitudes and theoretical approaches to the meaning as such, use different concepts and definitions, e.g., if the concept finding meaning and quest of meaning means the same; regarding the problem of definitions, authors chose too distinct methods in their studies. During the last twenty years when attention to the quest or reconstruction of meaning after a traumatic loss is under investigation, there are quite a lot of results found, a huge variety of knowledge in this field; thus, it is needed to be able to generalize it. A more clear view to the quest or the reconstruction of meaning after a traumatic loss is important not only to scientists but also to practicians dealing with people surviving a traumatic loss of significant others as well. In this article, the main trends of researching the quest or reconstruction of meaning after a traumatic loss and the difficulties in comparing and generalizing the results of these different studies are discussed.
Keywords: grief; meaning reconstruction; finding meaning; meaning-making; traumatic loss